Lithium manganese iron phosphate materials: Design, progress, and challenges - Huilong Zeng; Yuanxin Wan; Shuzhang Niu; Xiao Yu; Zerui Chen; Boqiao Li; Dongju Fu; Peigang Han; Jun Liu (Energy Materials and Devices)
With the boom in electric vehicles (EVs), there is an increasing demand for high-performance lithium-ion batteries. Lithium manganese iron phosphate (LMFP) has emerged as an enhanced variation of LiFePO4 (LFP), offering an energy density 10%–20% greater than that of LFP. Structural distortion caused by the Jahn–Teller effect decreases the capacity and voltage platform, thus restricting the commercialization of this material. Herein, ideas to overcome these challenges, including the crystal structure of LMFP and strategies to mitigate the Jahn–Teller distortion, are first explored. Then, the migration pathways of Li+ during charging and discharging and the phase transition mechanisms that affect the material’s performance are discussed. Next, the optimal Mn:Fe ratio for achieving the desired performance is described. The influences of various synthesis and modification methods on the morphology and structure of LMFP are reviewed. Additionally, different modification techniques, such as doping and coating, to enhance the performance of LMFP are highlighted. Finally, an overview of the current state of research on the recycling and reuse of LMFP is provided. By addressing these key topics, this paper offers a theoretical foundation for the further development of LMFP, thus contributing to its eventual commercialization.